Why is Bitcoin not Money? A Post-Keynesian view - Vianna, Matheus Trotta (Brazilian Keynesian Review, 2021)
Bitcoin got increasing popularity and was considered by the public as a great investment due to huge overvaluation in 2017. In parallel, economists and high-level technicians started to advocate the use of bitcoin and other cryptographic currencies as an alternative to national currencies. However, bitcoin is far from being considered as money, so it is hard for a monetary and payment system to emerge based on these technologies. This paper, apart from briefly presenting the Bitcoin System, shows why bitcoin is not money in the light of the Keynesian theory. We use Keynesian essential properties of Money and Modern Money Theory to define money, and to show that cryptographic currencies are not money. We then go back to Keynes’ theory of portfolio choice, established in Chapter 17 of the General Theory, to show what bitcoin really is: at most, bitcoin is a perfect virtual commodity, a virtual liquid speculative asset.